Anak Muda Memaknai Ruang Publik Di Kota Parepare, Sulawesi Selatan (Lembaga Pengembangan Kinerja Dosen, 2022)
Public spaces to be crucial and indispensable component of democratic civilizations. Public spaces are used for more than just leisure activities. However, public space has significance as a space to dialectics of society. Using a quantitative method and a descriptive analysis of the data gathered from 165 respondents, this study aims to give an overview of the youth in Parepare have begun to interpret public space to oversee many issue and policies. In addition, the youth of parepare also have the opinion that public spaces should be accessible to anyone and utilized for the common good. However, the youth of Parepare contend that the government's alligments in preparing an equal public space for the community.